Assessment of the Water and Sediment Quality of Tropical Forest Streams in Upper Reaches of Baleh River, Sarawak, Malaysia, Subjected to Logging Activities - Ling, TY; Soo, CL; Sivalingam, JR; Nyanti, L; Sim, SF; Grinang, J (Hindawi, 2016)
The study of the impact of logging activities on water and sediment quality of Sarawak forest streams is still scarce despite Sarawak being the largest exporter of timber in Malaysia. This study was aimed at determining the water and sediment quality of forest streams in Sarawak and the potential impact of logging activities. In-situ parameters were measured, and water and sediment samples were collected at six stations before rain. Additionally, water quality was investigated at three stations after rain. The results showed that canopy removal resulted in large temperature variation and sedimentation in the forest streams. Lower suspended solids were found at stations with inactive logging (< 2 mg/L) than active logging (10-16 mg/L) activities. The highest concentration of total nitrogen and total phosphorus in water and sediment was 4.4 mg/L, 77.6 µg/L, 0.17%, and 0.01%, respectively. Besides, significantly negative correlation of sediment nitrogen and water total ammonia nitrogen indicated the loss of nitrogen from sediment to water. Water quality of the streams deteriorated after rain, in particular, suspended solids which increased from 8.3 mg/L to 104.1 mg/L. This study reveals that logging activities have an impact on the water quality of Sarawak forest streams particularly in rainfall events.